Correlation between Neutrophil gelatinase-associated lipocalin and ß2-Microglobulin with serum protein electrophoresis in multiple myeloma patients - Inas Nazeeh Abed; Hiba Abid Al-Hussein Hassan; Usama Salman Al Timari (Journal of the Pakistan Medical Association, 2023)
Objective: To find the correlation between neutrophil gelatinase-associated lipocalin and beta2-microglobulin in patients with multiple myeloma. Method: The case-control study was conducted from November 2021 to March 2022, after approval from ethics review committees of three major medical establishments in Baghdad, Iraq. There were randomly selected multiple myeloma patients of either gender with normal concentration of urea and creatinine in group A, multiple myeloma patients of either gender with increased concentration of urea and creatinine in group B and healthy controls in group C. Neutrophil gelatinase-associated lipocalin and beta2-microglobulin were assessed using enzyme-linked immunosorbent assay technique. Data was analysed using SPSS 26. Results: Of the 180 subjects, there were 60(33.3%) in each of the 3 groups, with each group having 40(66.5%) males and 20(33.3%) females, and overall age ranging 40-79 years. Protein electrophoresis in group A patients was significantly higher (p=0.001) in alpha1, beta and gamma globulin. Among group B patients, a highly significant increase (p=0.001) was noted in alpha1, alpha2, beta and gamma globulin. Beta2-microglobulin was a more sensitive and specific marker for renal injury than neutrophil gelatinase-associated lipocalin in myeloma patients(p<0.05). Conclusion: Beta2-microglobulin and neutrophil gelatinase-associated lipocalin were both more sensitive markers than serum urea and creatinine in the diagnosis of acute kidney injury in multiple myeloma patients. Keywords: Lipocalin, Creatinine, Multiple myeloma, Microglobulin, Urea, Electrophoresis, Globulins, Albumins, Enzyme, Immunosorbent assay, Kidney injury.